Investigations of Heat Exchange and Pressure Losses of Regenerative Air Heaters of New Design - V. А. Kudinov; A. Yu. Abramova; E. V. Volkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Results of experimental and theoretical research of heat exchange and hydraulics of cast-iron lattice stuffing of regenerative rotating air heater of new design are given in the paper. Criterial dependences of heat exchange and pressure losses on medium velocity have been obtained.